# Jackson E&m Homework 8 Solutions

• January 2021
• PDF

This document was uploaded by user and they confirmed that they have the permission to share it. If you are author or own the copyright of this book, please report to us by using this DMCA report form.

### More details

• Words: 4,408
• Pages: 7
1

Assignment 8 — Solutions 3/10/04 Problem 5.22 Choose coordinates so that the infinite plane is the x-y plane (z = 0) and the bar is at some infinitesimal distance h above the plane. From the discussion in §5.9C a hard ferromagnet is equivalent to a system with an effective ÷÷÷” ÷÷” ÷÷÷” magnetic current density. For M = M z` there is only the effective surface current K = M ä n` where n` is the unit normal to the vertical surface (in general a function of position, though most of you took the bar to be a cylinder. The important thing for now is that n` is perpendicular to z` ). Applying the results of 5.17 we see that the system is equivalent to an image current distribution with components scaled by Hmr - 1L ê Hmr + 1L (amongst other things). Since mr ª m ê m0 = ¶ for our case, this factor reduces to H1 - 1 ê mr L ê H1 + 1 ê mr L Ø 1. We see that all we need is the "reflected" current (recall that there is no z component since z` ä n` must lie in the x-y plane, and actually no zdependence at all since the bar is uniform in the z-direction) and corresponding image magnetization: ÷÷”* K Hx, y, zL = Kx Hx, y, -zL x` +K y Hx, y, -zL y` ÷÷÷” ÷÷÷”* M = M Image bar located with "top" end-cap at z = -h.

z

JJK M = M zˆ

h -h

z

A

µ0 nˆ

ϖ JJK * M

h

-------

-h

++++++++

ϖ

µ =∞

The field due to the image can be calculated from its magnetic scalar potential 5.99, but this is hard for a bar of arbitrary cross-section. Instead we look at things from the effective magnetic charge density point of view. For ÷÷÷” ÷÷÷” M = M z` = constant there is only the effective surface charge sM = H≤ z` L ÿ M = ≤M where the upper sign is for the upper end-cap and the lower for the lower end-cap. Since the bar is very long we will neglect the effect of the ÷÷÷”* * = H≤ z` L ÿ M = ≤M for the image bar, and we will upper end-cap. Similarly there are effective surface charges sM ignore the lower end-cap of this. In summary we have two surfaces with equal and opposite constant charge density as shown in the second diagram.

÷÷÷” Because the material is infinitely permeable, the H -field must be perpendicular to the z = 0 boundary. Now this is ÷ ” ÷÷÷” analogous to the electrostatic problem (with E Ø H and 1 ê e0 Ø m0 ) of a charge distribution above an infinite conducting plane and a corresponding image charge distribution below. As discussed in problem 2.9 of homework set 3 the force on a small patch of the image charge (which has normal z` ) is ÷” ÷” ÷” ÷ ”* * 2 ê 2L z` a for the F = ÅÅÅÅ1Å IE > + E < M s a = Hs2 ê 2 e0 L z` a for a conductor, and so by analogy F = Hm0 sM 2

magnetic case. The force on the magnetic charge must be equal and opposite, so

m0 m0 m0 ÷” ÷ ”* F = - ® F = - ® a ÅÅÅÅÅÅÅÅÅ s*M 2 z` = - ÅÅÅÅÅÅÅÅÅ M 2 z` ® a = - ÅÅÅÅÅÅÅÅÅ M 2 A z` 2 2 2 S S S

2

Problem 5.30 (a)

Let S denote the cylinder surface, then

I cos f ÷” ” £ J Hx L = KHfL dHv - RL z` , KHfL = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ 2R ÷” ” £ ÷” ” m J Hx L I cos f£ m0 ` 2 x£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ AHxL = ÅÅÅÅÅÅÅÅ0ÅÅ ‡ 3 x£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅ Å ÅÅÅÅ Å ÅÅÅ Å Å z  ÅÅÅÅÅÅÅÅÅ”ÅÅÅ£ÅÅÅÅÅ , x” £ = R cos f£ x` + R sin f£ y` + z£ z` = ‡ ” ” ” £ †x - x § 4p 4p 2 R †x - x § S

Expand using 3.149 where v< (v> ) is the smaller (larger) of v and R:

¶ i1 y ¶ 1 4 £ LD jjj ÅÅÅÅÅ £ LD I Hk v L K Hk v Lzzz k cos@kHz z Hk v L K Hk v L + cos@m Hf f I ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅ Å = ÅÅÅÅ Å ‚ j zz < > m < m > ‡ 0 j2 0 †x” - x” £ § p 0 k { m=1

÷” The A integral picks out the m = 1 term by orthogonality of cosines in the range 0 § f£ § 2 p. Using cos Hf - f£ L = cos f cos f£ + sin f sin f£ and the orthogonality of sines and cosines, the f£ integral is 2p 2p Ÿ0 f£ cos f£ cosHf - f£ L = cos f Ÿ0 f£ cos2 f£ = p cos f: 2p ¶ ¶ I cos f£ 4 m0 ÷” ” AHxL = ÅÅÅÅÅÅÅÅÅÅ z` ‡ R f£ ‡ z£ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ ‡ k cos@kHz - z£ LD cosHf - f£ L I1 Hk v< L K1 Hk v> L 4p 2R p 0 0 -¶ ¶ ¶ m0 I ` = ÅÅÅÅÅÅÅÅÅÅÅÅÅ z cos f ‡ z£ ‡ k cos@kHz - z£ LD I1 Hk v< L K1 Hk v> L 2p -¶ 0

¶ z£ ‰-Â k z From the d-function representation 2 p dHkL = Ÿ-¶ £ ¶ £ £ Â k z ¶ z£ ‰-Â k z M = Re@‰Â k z 2 p dHkLD: Ÿ-¶ z cos@kHz - z LD = ReI‰ Ÿ-¶

£

we

have

¶ ÷” ” AHxL = m0 I z` cos f ‡ k ReA‰Â k z dHkL I1 Hk v< L K1 Hk v> LE 0

Applying the asymptotic form 3.102 (since the arguments of I1 and K1 approach 0 due to the d-function): É ÄÅ ¶ 1 i k v< y GH1L ij 2 yzÑÑÑ ÅÅ Â k z ÷” ” ` j z Å j z AHxL = m0 I z cos f ‡ k ReÅÅ‰ dHkL ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ j ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ z ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÑÑÑ ÅÅÇ GH2L k 2 { 2 k k v> {ÑÑÖ 0 É É Ä ÄÅ Å 1 1 v< ÑÑÑ v< ÑÑÑ ` cos f ¶ k ReÅÅÅdHkL ÅÅÅÅÅÅÅÅ ` cos f ReÅÅÅ ¶ k dHkL ÅÅÅÅÅÅÅÅ Ñ ÑÑ ÅÅÅÅÅ m = ÅÅÅÅÅ m I z Å ÅÅÅ I z Å ÅÅÅ Ñ ÅÅ ÅÅ‡ = ‡ 0 0 ÅÅÇ ÅÅÇ -¶ 2 4 v> ÑÑÑÖ v> ÑÑÑÖ 0 v< 1 = ÅÅÅÅÅ m0 I cos f ÅÅÅÅÅÅÅÅÅÅÅÅ z` v> 4

It was necessary to double the range of so that we can properly integrate the d-function. Recall that v< ê v> = v ê R for v § R and v< ê v> = R ê v for v ¥ R. The nonzero terms in the curl are:

3

1 l ij o o ÅÅÅÅÅÅ , v§R jj o o jj ` 1 v< ` 1 ∑ Az ` ∑ Az 1 ÷” ÷” o R ÷” ` j B = “ ä A = v ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅ - f ÅÅÅÅÅÅÅÅÅÅÅÅÅ = ÅÅÅÅÅ m0 I jj-v ÅÅÅÅÅÅÅÅ sin f ÅÅÅÅÅÅÅÅÅÅÅÅ - f cos f m o jj o R v v ∑f ∑v 4 v> o jj o o - ÅÅÅÅÅÅÅÅÅÅ , v ¥ R k n v2 sin f ` cos f 1 l ` ÅÅÅÅÅÅÅÅ o o v ÅÅÅÅÅÅÅÅ + f ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ = ÅÅÅÅÅÅ y` , v § R o o 1 o R R R = - ÅÅÅÅÅ m0 I m o o R ` ` 4 o o , v¥R o ÅÅÅÅÅÅÅÅÅÅ Iv sin f - f cos fM n v2

| yz o o z o o ozzzz } zz o zz o o o ozz ~{

` + cos f f` we see by crossing v ` into it that the vector potential outside the cylinder is: From y` = sin f v ÷÷÷” 1 R 1 R ` ` m0 H-I R y` Läv ÷” ä y = ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ A> = ÅÅÅÅÅ m0 I ÅÅÅÅÅÅÅÅ cos f z` = ÅÅÅÅÅ m0 I ÅÅÅÅÅÅÅÅ v 4 v 4 v 4p v2

÷÷÷” ê v2 , we see that this is indeed a 2D dipole with dipole ÷÷” äv Comparing this to the 2D version of 5.55, Hm0 ê 4 pL m moment -I R y` . (b)

Since we're in free space, 5.148 gives for a cylinder of length :

1 1 ÷”2 ÷”2 3 x B + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ‡ 3 x B W = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ‡ 2 m0 v¥R 2 m0 v§R 1 m0 I 2 1 m0 I R 2 = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ‡ 3 x J- ÅÅÅÅÅÅÅÅÅÅÅÅÅ N + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ‡ 3 x J- ÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ N Isin2 f + cos2 fM 4R 4 v2 2 m0 v§R 2 m0 v¥R 2p  ¶ m0 I 2 R2 1 m0 I 2 3 x + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ‡ v f ‡ z ‡ v ÅÅÅÅÅÅÅÅÅÅ = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ‡ 32 R2 v§R 32 v4 0 0 R É Ä ÅÅ m0 I 2 R2 m0 p  I 2 m0 p  I 2 1 ÑÑ¶ m0 I 2 = ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ p R2  + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ 2 p  ÅÅÅÅ- ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÑÑÑÑ = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÇ 2 v2 ÑÖR 32 R2 32 32 32

We see that this is equally distributed between inside and outside the cylinder, and that th energy per unit length is W m0 p I 2 ÅÅÅÅÅÅÅÅÅ = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ 16  (c)

Since we have only one circuit W = L I 2 ê 2. Comparing to the above we read off L ê  = p m0 ê 8.

Problem 5.33 (a)

÷” Following the arrows on the diagram we see that x” 12 = -x” 2 + R + x” 1 , so

4

” ” l 1 ÿ l 2 x” 12 m0 ÷” F 12 = - ÅÅÅÅÅÅÅÅÅÅ I1 I2 ® ® ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ 4p †x” 12 §3 ” ” ÷” l 1 ÿ l 2 Ix” 1 - x” 2 + RM m0 ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ = - ÅÅÅÅÅÅÅÅÅÅ I1 I2 ® ® ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÷”ÅÅÅÅÅÅÅÅ 3 4p °x” 1 - x” 2 + R• ” ” ij ÷ ” m0 l 1 ÿ l 2 yzz j = - ÅÅÅÅÅÅÅÅÅÅ I1 I2 ® ® jjj-“R ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÷ÅÅÅÅ ”ÅÅ zzz 4p °x” 1 - x” 2 + R• { k ” ” l 1 ÿ l 2 yzz ÷ ” ijj m0 j = I1 I2 “R jj ÅÅÅÅÅÅÅÅÅÅ ® ® ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅ z ” - x” + ÷R”• zz 4 p °x 1 2 { k ÷” ÷” = I1 I2 “R M12 HRL

I1

K dlK1 x1

K x12

JK R

K dl 2

K x2

I2

÷” We've pulled the “R out because it's not a function of the integration variables. (b) ÷” “2R M12 HRL =

” ” ” ” m0 l 1 ÿ l 2 l 1 ÿ l 2 m0 2 2 ÅÅÅÅÅÅÅÅÅÅ “R ® ® ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÷ÅÅÅÅ ”ÅÅ = ÅÅÅÅÅÅÅÅÅÅ ® ® “R ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÷ÅÅÅÅ ”ÅÅ 4p 4p °x”1 - x” 2 + R• °x” 1 - x” 2 + R•

÷” Change integration variables x” 1 Ø x” ª x” 1 - x” 2 , and rename R ª -x” £ to put this into a form we recognize:

m0 1 1 m0 ” ” ” ” ÷” ÅÅÅÅÅ = ÅÅÅÅÅÅÅÅÅÅ ® ® l 1 ÿ l 2 “£2 ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ = 0 “2R M12 HRL = ÅÅÅÅÅÅÅÅÅÅ ® ® l 1 ÿ l 2 “2R ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÷ ” ” †x 4p 4p x” £¨¨¨§ Æ °x” + R• ´¨¨¨¨¨¨¨¨¨¨¨¨¨≠ ¨¨¨¨¨¨¨¨ 0

1 ” ”£ 3 ” ”£ Actually “£2 ÅÅÅÅÅÅÅÅ ÷” Å÷ÅÅÅ”Å£ÅÅÅÅ = -4 p d Hx - x L, but a little thought shows that x ∫ x over the range of integration. † x-x §

Problem 6.11 (a) Consider the total electromagnetic momentum contained in an infinitesimal volume swept out by the infinitesimal area DA in time Dt by the wave (which has speed c): ÷” DP = momentum densityäareaälength = ÷g” DA c Dt

÷” ÷ ” DP From conservation of momentum, the force is due to the transfer of this momentum, F = ÅÅÅÅ ÅÅÅÅÅ = ÷g” DA c. The Dt pressure P is perpendicular force per unit area. For normally incident radiation ÷g” is already perpendicular, so

S energy time P = g c = ÅÅÅÅÅ = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ä ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ = energy per unit volume c areaä time length (b)

We are given S º 1.4 kW ê m2 . From Newton's law the acceleration due to the radiation pressure is

5

force pressureä area S A 1.4 kW ê m2 1 arad = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅ = ÅÅÅÅÅ ÅÅÅÅÅÅ º ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ º 4.67ä 10-3 m ë s2 mass mass c m 3.0ä108 m ê s 1 g ê m2 According to http://pluto.space.swri.edu/IMAGE/glossary/solar_wind.html the solar wind particle density averages (rounding up) 10 protons ê cm3 and has average speed 500 km ê s. If all of the kinetic energy is transferred to the solar sail, this would cause an acceleration 1 A 1 10ä1.67ä10-22 kg 1 2 awind = ÅÅÅÅÅ Hwind densityLäHwind speedL2 ÅÅÅÅÅÅ º ÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ä I500ä103 m ê sM ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ 3 2 m 2 1 g ê m2 H10-2 mL º 2.09ä10-6 m ë s2 ` arad H! L

Problem 6.20 (a)

Plugging in the given charge density into 6.23:

rHx” , tL = dHxL dHyL d£ HzL dHtL ÷” Jz Hx” , tL = -dHxL dHyL dHzL d£ HtL , J Hx” , tL = Jz Hx” , tL z` rHx”£ , tL 1 1 1 ” 3 £ 3 x£ dHx£ L dHy£ L d£ Hz£ L dHtL ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅ Å Å ÅÅÅÅÅÅÅÅ Å ÅÅÅ Å ÅÅÅ Å Å  x  ÅÅÅÅÅ = ÅÅÅÅÅÅÅÅ Å ÅÅÅ Å ÅÅÅ Å Å FHx, tL = ‡ ‡ ” ” ” †x - x£ § 4 p e0 †x - x” £ § 4 p e0

Recall that Ÿ z d£ HzL f HzL = - f £ H0L which follows from integration by parts, and using the usual formula ∑†b x” - c”§n ê ∑†x” § = n †b x” - c”§n-2 Hb †x” § - c” ÿ x` L together with r ª †x” §: ” ` 1 1 1 1 z ij -z£ - x ÿ z yz yz i ∑ j z ÅÅÅÅ Å ÅÅÅ Å Å = ÅÅÅÅÅÅÅÅ Å ÅÅÅ Å ÅÅÅ Å Å dHtL ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅ z = - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ dHtL ÅÅÅÅÅÅÅÅ FHx” , tL = - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ dHtL jj ÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ` ” ` ” 4 p e0 4 p e0 4 p e0 r3 k ∑ z£ †x - z£ z§ {z£ =0 k †x - z£ z§3 {z£ =0

(b)

The transverse current is given by 6.25 and 6.29:

1 ÷ ” ∑F 1 ê c2 ÷ ” ÷” ÷” ÷” ÷” J t = J - J l = J - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ “ ÅÅÅÅÅÅÅÅÅÅ = -dHxL dHyL dHzL d£ HtL z` + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ “ Jd£ HtL m0 c2 ∑t 4 p m0 e0

z ÅÅÅÅÅÅÅÅ N r3

Following the derivation of 4.20 we see that we can't just take the naïve gradient of z ê r3 without adding a d -function term. In fact if we take ÷p” ª z` in 4.20 we get (remember that 4.20 is the negative gradient of the dipole term in 4.10, with the correct addition): ` ÷” ` ÷” 3 r` Hz` ÿ r` L - z` ÷” z 4p 4p y i 3 r H p ÿ rL - p “ ÅÅÅÅÅÅÅÅ = - jj ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ - ÅÅÅÅÅÅÅÅÅÅ ÷p” dHx” Lzz = - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅ z` dHx” L 3 3 3 r 3 3 r r { k ` ` ` ` 1 4p ÷” i 3 r Hz ÿ rL - z y J t = -dHx”L d£ HtL z` + ÅÅÅÅÅÅÅÅÅÅ d£ HtL jj- ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅ z` dHx” Lzz 3 r 4p 3 k { ` z 3 2 i y = -d£ HtL jj ÅÅÅÅÅ dHx” L z` - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ r` Hz` ÿ r` Lzz 3 3 4 3 p r p r 4 k {

6

÷” ÷” (c) As mentioned in the last paragraph of §6.3 A is manifestly causal (thus so is B since that is completely ÷” ÷” ÷” ÷” specified by A ), so we need only worry about F and by extension E = -“ F - ∑ A ë ∑t . Using 6.48 and the hint: 1 ÷” m ÷” A = ÅÅÅÅÅÅÅÅ0ÅÅ ‡ 3 x£ ÅÅÅÅÅÅ AJ Hx” £ , t£ LE , @ Dret ª 4p R ret 1 ÷” ∑ 1 y ÷” ” i J t Hx, tL = -d£ HtL jjdHx” L z` + ÅÅÅÅÅÅÅÅÅÅ “ ÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ zz 4 p ∑z r { k ÷” m0 1 ∑ ÄÅÅ R i ∑A ÅÅÅÅÅÅÅÅÅÅ = - ÅÅÅÅÅÅÅÅÅÅ ‡ 3 x£ ÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅ ÅÅÅÅd£ Jt - ÅÅÅÅÅÅ N jjdHx” £ L z` + ∑t 4p R ∑t ÇÅ c k

@ Dt£ =t-Rêc , R ª †x” - x” £ §

1 ÷ ”£ ∑ 1 yÉÑÑ ÅÅÅÅÅÅÅÅÅÅ “ ÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅ zzÑÑÑÑ ∑ z£ r£ {ÑÖ 4p

¶ k ‰Â k Ht-RêcL to rewrite the second: Use the d Hx” £ L to integrate the first term and 2 p dHt - R ê cL = Ÿ-¶

÷” ∑A R m0 k 1 ∑2 1 ÷ ”£ ∑ 1 m0 1 ÅÅÅÅÅÅÅÅÅÅ = - ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ d≥ Jt - ÅÅÅÅÅÅ N - ÅÅÅÅÅÅÅÅÅÅ ‡ 3 x£ ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅ ‰Â k Ht-RêcL ÅÅÅÅÅÅÅÅÅÅ “ ÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅ ∑ z£ r£ 4p r c 4p 2 p R ∑t2 4p ∑t

‰Â k Ht-RêcL 1 1 “£2 ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ = ÅÅÅÅÅÅ “£2 ‰Â k Ht-RêcL + ‰Â k Ht-RêcL “£2 ÅÅÅÅÅÅ R R R 1 = ÅÅÅÅÅÅ H-Â k ê cL2 ‰Â k Ht-RêcL - ‰Â k Ht-RêcL 4 p dHx” - x”£ L R 1 ∑2 ‰Â k Ht-RêcL = ÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ - ‰Â k t 4 p dHx” - x” £ L c2 ∑t2 R ÷” ∑A m0 1 m0 c2 k ÅÅÅÅÅÅÅÅÅÅ = - ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ d≥ Ht - R ê cL z` - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ‡ 3 x£ ÅÅÅÅÅÅÅÅÅÅ ∑t 4p r 4p 2p

ij £2 ‰Â k Ht-RêcL y ÷ ”£ ∑ 1 jj“ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ + ‰Â k t dHx” - x” £ Lzzz “ j z ÅÅÅÅÅÅÅÅÅ£ÅÅÅ ÅÅÅÅ£ÅÅ ∑z r 4pR k {

Using d Hx” - x” £ L to integrate the last term, the remaining integral over ‰Â k t produces a d-function. We also use Green's theorem (discarding boundary terms since the boundary is at infinity) to shift the Laplacian in the second term over to the 1 ê r£ , producing another d-function [remember the normalization “£2 H1 ê r£ L = -4 p d3 Hx” £ L]: ÷” ∑A m0 1 R m0 ÅÅÅÅÅÅÅÅÅÅ = - ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ d≥ Jt - ÅÅÅÅÅÅ N z` - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ∑t 4p r c 4 p m0 e0

ij 1 k ‰Â k Ht-RêcL ÷ ”£ ∑ ÷” ∑ 1 y jj‡ 3 x£ ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ “ ÅÅÅÅÅÅÅÅÅÅÅÅ “£2 ÅÅÅÅÅÅ + dHtL “ ÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ zzzz j ∑z r { ∑ z£ r£ 2p 4pR k m0 1 1 k ‰Â k Ht-RêcL ÷ ”£ ∑ 1 ÷” z = - ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ d≥ Ht - R ê cL z` + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ‡ 3 x£ ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ “ ÅÅÅÅÅÅÅÅÅÅÅÅ dHx” £ L - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ dHtL “ ÅÅÅÅÅÅÅÅ £ ∑z 4p r 4 p e0 2p R 4 p e0 r3

÷ ”£ Again we integrate the second term by parts to move the “ ÅÅÅÅ∑ÅÅÅÅ£Å away from the d-function. We want to use the ÷ ”£ ÷ ” ∑z latter to do the x£ integral, but first we rewrite “ ÅÅÅÅ∑ÅÅÅÅ£Å Ø I-“M I- ÅÅÅÅ∑ÅÅÅÅ M so we can pull it out of the x£ integral: ∑z

÷” ∑A m0 1 1 k ÅÅÅÅÅÅÅÅÅÅ = - ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ d≥ Ht - R ê cL z` + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ‡ 3 x£ ÅÅÅÅÅÅÅÅÅÅ ∑t 4p r 4 p e0 2p

∑z

ij÷ ” ∑ ‰Â k Ht-RêcL yz ” £ 1 ÷” z jj“ ÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zz dHx L - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ dHtL “ ÅÅÅÅÅÅÅÅ j z R 4 p e0 r3 k ∑z { k ÷ ” ∑ ‰Â k Ht-rêcL m0 1 1 1 ÷” z = - ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ d≥ Ht - R ê cL z` + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ‡ ÅÅÅÅÅÅÅÅÅÅ “ ÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ dHtL “ ÅÅÅÅÅÅÅÅ r3 2 p ∑z 4p r 4 p e0 r 4 p e0

7

Ä É Ä ÉÑ ‰-Â k rêc yz i ∑ yÑÑÑÑ 1 y ÷ ” ∑ ‰-Â k rêc ÷ ” ÅÅÅÅijj Â k ‰-Â k rêc ÷ ” ÅÅ Ñ i Âk j z “ ÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ = “ ÅÅÅjj- ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zzz j ÅÅÅÅÅÅÅÅÅ rzÑÑÑ = -“ ÅÅÅÅ‰-Â k rêc jj ÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅ zz cos qÑÑÑÑ ÅÇ ÑÖ ÅÅÇk r ∑z cr r2 { k ∑ z {ÑÑÖ r2 { k cr ÄÅ Â k É 1 yi Âk y i Âk 2 yÑÑ ÷” Åi i Âk = - ÅÅÅÅjj ÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅ zz jj- ÅÅÅÅÅÅÅÅÅ zz + jj- ÅÅÅÅÅÅÅÅÅÅÅÅÅ - ÅÅÅÅÅÅÅÅ zzÑÑÑÑ cos q ‰-Â k rêc “ r - ‰-Â k rêc jj ÅÅÅÅÅÅÅÅÅ + 2 2 3 ÅÇk c r Ñ r {k c { k cr r {Ö k cr jij ÅÅÅÅ2ÅÅÅÅ + jj 3 kr ÅÄÅ Â k Åi = ÅÅÅÅjj ÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÇk c r2

1 y ÷” ÅÅÅÅÅÅÅÅ zz “ cos q r2 {

1 y i sin q ` y 2Âk k2 y i Âk ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ - ÅÅÅÅÅÅÅÅÅÅÅÅÅ zzzz cos q ‰-Â k rêc r` - ‰-Â k rêc jj ÅÅÅÅÅÅÅÅÅ + ÅÅÅÅÅÅÅÅ zz jj- ÅÅÅÅÅÅÅÅÅÅÅÅÅÅ qzz 2 2 r r2 { k cr c r{ { k cr É Ñ ÑÑ 1 y k2 ` + ÅÅÅÅÅÅÅÅ zz I2 cos q r` + sin q qM - ÅÅÅÅÅÅÅÅÅÅÅÅÅ cos q r` ÑÑÑÑ ‰-Â k rêc ÑÑÖ r3 { c2 r ÷” Now when we plug this back into the integral in ∑ A ë ∑t we can convert it all back to d-functions by using the ¶ k Fourier transform formula F HnL HwL = Ÿ-¶ ÅÅÅÅÅÅÅÅÅ H-Â kLn f HkL ‰Â w k with F Ø d, f Ø 1, w Ø t - R ê c for our case: =

2p

÷” ∑A m0 1 1 ÄÅÅi 1 ÅÅÅÅÅÅÅÅÅÅ = - ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ d≥ Ht - R ê cL z` + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅjj- ÅÅÅÅÅÅÅÅÅÅÅÅÅ d£ Ht - R ê cL + ∑t 4p r 4 p e0 ÅÇk c r2 ÉÑ 1 1 ÷” z Ñ + ÅÅÅÅÅÅÅÅÅÅÅÅÅ d≥ Ht - R ê cL cos q r` ÑÑÑÑ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ dHtL “ ÅÅÅÅÅÅÅÅ ÑÖ 4 p e r3 c2 r

1 ` y ÅÅÅÅÅÅÅÅ dHt - R ê cLzz I2 cos q r` + sin q qM 3 { r

c ÄÅÅi 1 1 ` ` y = - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ d≥ Hc t - RL Icos q r` - sin q qM + ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅjj- ÅÅÅÅÅÅÅÅ d£ Hc t - RL + ÅÅÅÅÅÅÅÅ dHc t - RLzz I2 cos q r` + sin q qM { 4p r 4 p e0 ÅÇk r2 r3 ÑÉÑ 1 1 ÷” z + ÅÅÅÅÅ d≥ Hc t - RL cos q r` ÑÑÑÑ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ dHtL “ ÅÅÅÅÅÅÅÅ ÑÖ 4 p e0 r3 r 1 c ÅÄÅi 1 1 1 ` ` ÑÉÑ ÷” z y = - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ ÅÅÅÅjj ÅÅÅÅÅ d£ Hc t - RL - ÅÅÅÅÅÅÅÅ dHc t - RLzz I2 cos q r` + sin q qM - d≥ Hc t - RL sin q qÑÑÑÑ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ dHtL “ ÅÅÅÅÅÅÅÅ 2 ÑÖ 4 p e0 { r3 4 p e0 r ÇÅk r r 0

m0 c3 1

In the second step I've used an identity for d-functions d Ha xL = d HxL ê †a§ to rewrite d Ht - R ê cL = c d Ht - R ê cL, then ÷” ÷” ÷” ÷” ÷” ÷” ∑A ∑A every derivative costs a factor of c. Now plug this into E = -“ F - ÅÅÅÅ ÅÅÅÅÅ = ÅÅÅÅÅÅÅÅ1ÅÅÅÅÅÅÅÅ d HtL “ ÅÅÅÅz3ÅÅ - ÅÅÅÅ ÅÅÅÅÅ , where the “ ÅÅÅÅz3ÅÅ ÷” ∑A cancels the one from ÅÅÅÅ ÅÅÅÅÅ : ∑t

∑t

4 p e0

r

∑t

r

É 1 dHc t - RL y c ÄÅÅi d£ Hc t - RL ` ` ÑÑ ÷” E = ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅ ÅÅÅÅjj ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ - ÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅÅ zz I2 cos q r` + sin q qM - d≥ Hc t - RL sin q qÑÑÑÑ ÑÖ 4 p e0 r ÅÇk r r2 {

The Cartesian components is straightforward plug-in of r` = cos f sin q x` + sin f sin q y` + cos q z` and ` q = cos f cos q x` + sin f cos q y` - sin q z` . The result is a not-very-enlightening mess that will just be retyping the stuff in Jackson, so instead I'll outline the procedure in words. Looking at the x component we see that the relevant ` parts of r` and q all get multiplied by cos f and the correct factor of either sin q or cos q to enable us to pull the angular terms out. The first and second term then adds to give the factors of 3 that appear in the formula, and the signs are exactly as they should be. The y component works the same way. For the z component each of the cosines and sines gets squared and the sines flip sign. The last term immediately produces what we want. The second term can be converted to cosines using sin2 q + cos2 q = 1, which gives the factor of 3 cos2 q - 1. ÷” Anyway, we see from the d-functions above that E is manifestly causal (t doesn't appear anywhere else).

January 2021 1
February 2021 0
February 2021 0
February 2021 0
February 2021 1
January 2021 1

January 2021 1